A 3D CFD model of novel flow channel designs based on the serpentine and the parallel design for performance enhancement of PEMFC. (1st November 2022) - Rostami, Leila; Haghshenasfard, Masoud; Sadeghi, Morteza; Zhiani, Mohammad
Abstract: The flow field design is one of the crucial factors that directly affects on the proton exchange membrane (PEM) fuel cell performance. To increase mass transfer, water management, and cell performance, a novel design inspired by serpentine and parallel topologies is proposed. The principal criteria of this design are focused on pressure drop reduction and a more uniform distribution of the reactants via the flow fields. To achieve these objectives, 3D PEMFC models are analyzed using the computational fluid dynamic (CFD) technique for the novel (called V-Ribbed) and common flow fields. The results showed that the pressure and the velocity distributions are more uniform in the V-Ribbed design compared with the other cases. More oxygen penetration at the cathode electrode surface is seen when liquid water within V-Ribbed channels is reduced. This causes to improve the electro chemical reaction rate, current density, and cell efficiency. It is found that using V-Ribbed channels increased the average current flux density on the cathode side about 41.5% and 21.88% compared to serpentine and parallel channels, respectively. Furthermore, the results of the polarization curve showed an enhancement of 2.19% and 2.5% in V-Ribbed design compared to serpentine and parallel channels, respectively. Highlights: Pressure drop in the parallel flow channels is lower than in other flow fields. Water content in the V-Ribbed design was higher than in conventional designs. Performance of the V-Ribbed flow channels is 3.5% higher than the parallel design.